The Effect of Nitrogen and Salinity on The Content of Chlorophyll-a Dunaliella salina - Fajar, Achmad (Journal of Aquaculture Development and Environment, 2023)
Dunaliella salina is one of the microalgae that has the potential to be utilized because it has a fairly high nutritional content as much as 57% protein, 32% carbohydrate, 6% lipid, and 5% chlorophyll pigment. Chlorophyll produced by microalgae is inseparable from salinity and nitrogen because when microalgae carry out photosynthetic activities, microalgae need nitrogen as a nutrient for building material for the chlorophyll-a pigment network. This study aims to determine the effect and best concentration of nitrogen and salinity on the chlorophyll-a content of D. salina microalgae. The method used was a factorial design (FD), namely salinity 25ppt, 30ppt, 35ppt, and 40ppt and nitrogen concentrations in modified walne media, namely 100%, 75%, 50%, 25%. Data analysis in this study used the Anava Test and continued with the Duncan Test. The data obtained were analyzed by Anava Test followed by Duncan's Test showing significant results. The highest chlorophyll-a content was at 35 ppt nitrogen 50% salinity with 8,268 mg/mL chlorophyll-a content and the lowest chlorophyll-a content at 40 ppt nitrogen 25% salinity treatment was 2,351 mg/mL. At a nitrogen concentration of 50% there was an increase in the chlorophyll-a content, while the nitrogen concentration of 100% and 75% of microalgae decreased the content of chlorophyll-a. At a nitrogen concentration of 25%, there was no increase in the chlorophyll-a content because under conditions of nitrogendeficiency, the formation of chlorophyll would decrease, causing the process of photosynthesis to be hampered. Based on the research, it can be concluded that differences in nitrogen concentration and salinity can affect the chlorophyll-a content ofD. salina.